Antioxidant and antimicrobial potential of tilapia gelatin coating containing pepper extract - Alfaro, Alexandre da Trindade; Piva, Daiane; Balbinot-Alfaro, Evellin; Machado-Lunkes, Alessandra (Pesquisa Agropecuaria Brasileira, 2026)
The objective of this work was to evaluate tilapia gelatin with pepper extract as a sausage coating, applied through immersion and spraying. The treatments were: control (without coating), coating by immersion and spraying, and coating with the extract by immersion and spraying. The pepper extract showed a high phenolic content (217.9 mg gallic acid equivalents per gram) and antioxidant activity. All coated sausages presented a lower peroxide index than the control. The sausages coated with pepper extract showed a lower oxidation rate. However, no significant differences were observed between the application methods and antimicrobial activity of the coatings. Tilapia gelatin with pepper extract as a coating has proven to be an alternative to reduce lipid oxidation in meat products and preserve their quality.